دور الابتكار في تعزيز الميزة التنافسية لمصرف أبو ظبي الإسلامي - بن عطاء الله, عادل; سلطاني, محمد رشدي (Recherches économiques et managériales, 2020)
تهدف هذه الدراسة إلى بيان دور الابتكار في تعزيز الميزة التنافسية لمصرف أبو ظبي الإسلامي، ودراسة الابتكار الذي ينشأ نتيجة رغبة المصارف الإسلامية في التخلص من القيود التي تحول دون تحقيق أهدافها، وذلك بتطوير منتجات قائمة أو استحداث أخرى جديدة تضمن لهذه المصارف قدرا من المرونة وتعزز ميزتها التنافسية مما يساعدها على الاستمرار بفعالية، وقد خلصت الدراسة إلى أن جوهر الصناعة المالية في المصارف الإسلامية هو الابتكار والتجدد.   الكلمات المفتاحية: الإبتكار - المصارف الإسلامية – الميزة التنافسية Summary:       This study aims to show the role of innovation in enhancing competitive advantage of Abu Dhabi Islamic Bank (ADIB), and studying the innovation that arises as a result of the desire of Islamic banks to get rid of the barriers to achieving their goals by developing existing products or introducing new ones that guarantee these banks a degree of flexibility and back up their competitive advantage. In order to continue effectively, and this study concluded that the core of financial industry in Islamic banks is innovation and renewal. keywords: Innovation - Islamic Banks - Competitive Advantage